MUTU NATA DE SEAWEED (Gracilaria Sp) DENGAN PENAMBAHAN SARI BELIMBING WULUH (Averrhoa bilimbi) DAN UREA PADA KONSENTRASI DAN JUMLAH YANG BERBEDA - Yanto, Supri; Agustini, Tri Winarni; Dewi, Eko Nurcahya (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Nata de seaweed is one of foods gelling products resulted from seaweed fermentation. Theaddition of bilimbi extract and urea are important factor to control pH and nitrogen resourcefor growing of A. xylinum in nata’s medium. The aims of research were to determine the bestconsentration by the addition of bilimbi as pH control substances and urea as nitrogenresources at different concentration to the nata de seaweed Gracilaria Sp. The research usingCompletely Randomized Factorial 2x2 design. The first factor is bilimbi extract with level of(3% and 4%) and the second factor is urea with level of (1 g and 1.5 g). The best treatment isthe addition of extract b. wuluh 3% and 1 g of urea with the quality characteristics of pH(4.07), yield (93.33 g), fiber content (0.93%), moisture content (95.06%), elasticity (1.26 mm/ g / s), sugar (6.05%), as well as preference test is fairly like to the product (appearance =6.4; flavor = 6.6; texture = 6). Examinations of F-test (ANOVA) showed that the addition ofextract bilimbi (3% & 4%) and urea (1 g and 1.5 g) gave a very significant (p<0,01) effect onthe yield, actual pH and moisture content of product and not significant (p>0,05) effect to thelevels of sugar, elasticity and fiber content.